Predictors of total morbidity burden on days 3, 5 and 8 after cardiac surgery. Issue 1 (December 2017) - Sanders, Julie; Cooper, Jackie; Mythen, Michael; Montgomery, Hugh
Abstract Background Post-operative morbidity affects up to 36% of cardiac surgical patients. However, few countries reliably record morbidity outcome data, despite patients wanting to be informed of all the risks associated with surgery. The Cardiac Post-Operative Morbidity Score (C-POMS) is a new tool for describing and scoring (0–13) total morbidity burden after cardiac surgery, derived by noting the presence/absence of 13 morbidity domains on days 3, 5, 8 and 15. Identifying modifiable C-POMS risk factors may suggest targets for intervention to reduce morbidity and healthcare costs. Thus, we explored the association of C-POMS with previously identified predictors of post-operative morbidity. Methods A systematic literature review of pre-operative risk assessment models for post-operative morbidity was conducted to identify variables associated with post-operative morbidity. The association of those variables with C-POMS was explored in patients drawn from the original C-POMS study (n  = 444). Results Seventy risk factors were identified, of which 56 were available in the study and 49 were suitable for analysis. Numbers were too few to analyse associations on D15. Thirty-three (67.3%) and 20 (40.8%) variables were associated with C-POMS on at least 1 or 2 days, respectively. Pre-operative albumin concentration, left ventricular ejection fraction and New York Heart Association functional class were associated with C-POMS on all days. Of the 16 independent risk factors, pre-operative albumin and haemoglobin concentrations and weight are potentially modifiable. Conclusions Different risk factors are associated with total morbidity burden on different post-operative days. Pre-operative albumin and haemoglobin concentrations and weight were independently predictive of post-operative total morbidity burden suggesting therapeutic interventions aimed at these might reduce both post-operative morbidity risk and health-care costs in patients undergoing cardiac surgery.